2017
DOI: 10.12681/eh.11515
|View full text |Cite
|
Sign up to set email alerts
|

Temperature dependent development of Phenacoccus solenopsis under laboratory conditions

Abstract: Cotton mealybug, Phenacoccus solenopsis Tinsley (Hemiptera: Pseudococcidae) is an important cotton pest in Punjab, India. Development of the immature stages (four instars in female and five in male) of P. solenopsis was observed at nine constant temperatures (15, 18, 20, 25, 30, 34, 35, 38, 40°C). Using the linear model, the lower temperature threshold (t min ) for development was estimated to be 4.93 and 2.95°C and the thermal constant (K) was 333.33 and 454.54 degree days for female and male, respectively. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 11 publications
1
1
0
Order By: Relevance
“…After that eggs hatching to immature stages P. solenopsis exhibited variation in males and females at immature stages. Our findings were agreed with the results of Kumar and Kontodimas (2012) who reported that egg development times (mean ± SE) ranged from 3.40±0.24, 2.10±0.33 and 1.10±0.24 days at 20, 25 and 30˚C, respectively.…”
Section: Egg Incubation Periodssupporting
confidence: 93%
“…After that eggs hatching to immature stages P. solenopsis exhibited variation in males and females at immature stages. Our findings were agreed with the results of Kumar and Kontodimas (2012) who reported that egg development times (mean ± SE) ranged from 3.40±0.24, 2.10±0.33 and 1.10±0.24 days at 20, 25 and 30˚C, respectively.…”
Section: Egg Incubation Periodssupporting
confidence: 93%
“…A number of studies of the biology of P. solenopsis have been conducted in recent times (Fand & Suroshe, 2015). The biology of P. solenopsis has been studied under different temperature conditions by several research groups (Kumar & Kontodimas, 2012;Prasad et al, 2012;Kumar et al, 2013). In addition, host plant suitability has been studied (Çalışkan et al, 2016;Dogar et al, 2018;Nagrare et al, 2018).…”
Section: Introductionmentioning
confidence: 99%